THU0627-HPR Exercise Therapy in Patients with Knee Osteoarthritis and Severe Pain is Enabled by Optimization of Analgesics – a Feasibility Study. (9th June 2015) - van Tunen, J.A.C.; van der Leeden, M.; Bos, W.; Cheung, J.; van der Esch, M.; Gerritsen, M.; Peter, W.F.; Roorda, L.D.; Tijhuis, G.J.; Voorneman, R.; Lems, W.F.; Dekker, J.
Abstract : Background: Severe pain in patients with knee OA hampers the ability to exercise. A protocol for the optimization of analgesics in combination with exercise therapy was developed. The purpose of this protocol is to reduce pain and thereby allowing the patient to participate in exercise therapy. Objectives: The objective of the present study was to evaluate the feasibility and outcome of the protocol. Methods: Forty-nine patients with knee OA and severe knee pain (NRS-pain≥7, range 0-10) were included in this study. Analgesics were prescribed following an incremental protocol. The incremental steps were (1) acetaminophen, (2) NSAIDs, (3) weak opioids and (4) intra-articular steroid injections. After six weeks of analgesic use a supervised exercise therapy program for 12 weeks was added, consisting of muscle strengthening exercises and training of daily activities. Knee pain was assessed with NRS-pain and activity limitations were assessed with WOMAC-PF. Data were collected at baseline, after six weeks, and after 18 weeks. Results: In intention-to-treat analyses statistically significant improvements in pain and activity limitations were found after six weeks of analgesic use and after the complete intervention. Mean improvements from baseline were 30% (p<0.001) for pain and 16% (p<0.001) for activity limitations after the complete intervention. Eighty-two percent of the patients were able to exercise according to the protocol. In these patients exercise therapy following on six weeks of analgesic use resulted in a further improvement of activity limitations of 10% (p=0.004). Conclusions: The combined intervention of analgesics and exercise therapy allows most patients with knee osteoarthritis and severe pain to participate in exercise therapy, leading to reduction of pain and activity limitations. These promising results need to be confirmed in a randomized controlled trial. Disclosure of Interest: None declared